Communication Strategy of The Makassar City Environmental Service in Waste Management - Muhammad Nuhung; Mujahid Mujahid; Andi Vita Sukmarini (Journal La Sociale, 2026)
This study aims to examine the communication strategy of Makassar City Environmental Agency in the government's efforts to address waste problems. This study aims to: (1) Analyze the communication strategy carried out by Makassar City Environmental Agency in waste management, (2) Identify supporting and inhibiting factors towards Makassar City Environmental Agency's communication strategy in waste management. The type of research used is qualitative research. The data in this study were obtained by conducting surveys and interviews with Makassar City Environmental Agency officials, waste bank management elements, Tamangapa Antang TPA managers and community elements. The results obtained from this study are: (1) Makassar City Environmental Agency has carried out waste management with the 3R (Reduce, Reuse, Recycle) waste management strategy, (2) waste management with waste banks, and (3) Waste management with mini-incinerators. In addition, the Makassar City government, through the Environmental Agency, plans long-term waste management by utilizing waste as electrical energy through the construction of PSEL or PLTSa or Waste to Energy Electricity Processing as a mitigation effort to address the waste problem in Makassar City. The communication strategy that the Makassar City Environmental Agency has implemented in waste management is by using mass communication through television, radio, newspapers, online media, and direct outreach to the community.